Impact of sugarcane bagasse-derived biochar on heavy metal availability and microbial activity: A field study. (June 2018) - Nie, Chengrong; Yang, Xing; Niazi, Nabeel Khan; Xu, Xiaoya; Wen, Yuhui; Rinklebe, Jörg; Ok, Yong Sik; Xu, Song; Wang, Hailong
Abstract: In the current study, we conducted a field experiment using the test plant, Brassica chinesis L. (pak choi), to investigate the effect of sugarcane bagasse-derived biochar on the bioavailability of cadmium (Cd), copper (Cu) and lead (Pb), and the health of soil microbiota in a contaminated soil. Biochar application significantly ( P  < 0.05) increased pak choi yield. Bioavailability of heavy metals to plant shoots and roots decreased with increasing biochar application rates (at 0, 1.5, 2.25 and 3.0 t ha −1 ). Sequential extraction of the biochar-treated and -untreated soil revealed that exchangeable Cd reduced whereas organically-bound fraction increased with increasing biochar rate. The labile fractions of Cu and Pb decreased, but the residual fraction increased in biochar-treated soils compared to the control. Urease, catalase and invertase activities, and the populations of bacteria and actinomycetes were significantly enhanced, whereas fungi population declined in biochar-treated soils. This study highlights that sugarcane bagasse biochar has the potential to support the remediation of soils contaminated with heavy metals, and as such can improve the yield and quality of agricultural crops. Highlights: Sugarcane bagasse biochar amendment reduced availability of Cd, Cu and Pb in soils. Heavy metals were less labile in the biochar-treated soils. Biochar amendment induced an increase in soil enzyme and microbial activity. Edible part of pak choi was safer for human consumption after biochar amendment.